1997
DOI: 10.1086/513628
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Risk Factors for Infection Due to Penicillin‐Resistant and Multidrug‐ResistantStreptococcus pneumoniae: A Multicenter Study

Abstract: Pneumococcal disease was studied prospectively to determine the risk factors associated with resistance to penicillin and other antibiotics. One hundred twelve clinically significant pneumococcal isolates were recovered from 95 patients. Approximately one-half (49.47%) of the cases were due to penicillin-resistant strains. Multivariate analysis showed that previous use of beta-lactam antibiotics (odds ratio [OR], 2.81; 95% confidence interval [CI], 0.95-8.27), alcoholism (OR, 5.22; 95% CI, 1.43-19.01), and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
61
3
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(76 citation statements)
references
References 6 publications
9
61
3
3
Order By: Relevance
“…Resistance to macrolide antibiotics, including the newer agents clarithromycin and azithromycin, was present in 48% of strains with high penicillin resistance. Risk factors for multidrug resistant S. pneumoniae include prior antibiotic use, extremes of age and hospitalization [79]. In two other recent large surveillance studies [80,81] beta-lactamase production was found in 33.4% of H. influenzae and 95% of M. catarrhalis.…”
Section: Antibiotic Resistance and New Antibiotics For Treatment Of Lmentioning
confidence: 97%
“…Resistance to macrolide antibiotics, including the newer agents clarithromycin and azithromycin, was present in 48% of strains with high penicillin resistance. Risk factors for multidrug resistant S. pneumoniae include prior antibiotic use, extremes of age and hospitalization [79]. In two other recent large surveillance studies [80,81] beta-lactamase production was found in 33.4% of H. influenzae and 95% of M. catarrhalis.…”
Section: Antibiotic Resistance and New Antibiotics For Treatment Of Lmentioning
confidence: 97%
“…One remarkable finding of the present investigation is that resistance rates showed pronounced variations between geographic regions and study centers within Germany. Major differences in beta-lactam resistance between children and adults have been reported in many other countries, and young age has been shown to be a risk factor for beta-lactam-resistant pneumococcal infection (2). In Germany only slight differences in beta-lactam resistance rates between children and adults were recorded.…”
mentioning
confidence: 89%
“…Children with sibling(s) were 66.7% 16) . There were 79.2% 19) patients who had taken beta -lactams and 20.8% 5) patients had taken macrolides within the past 3 months before the test. The mean term of antibiotic medication was 5 days.…”
Section: Characteristics Of Host Patientsmentioning
confidence: 99%
“…Worldwide, risk factors for the carriage of resistant S. pneumoniae have been well investigated in the last couple of decades [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and those studies reported that the most influencing factor was the previous use of antibiotics. Unnecessary use of antibiotics had been thought to cause this emergence of antibiotic resistant S. pneumoniae.…”
Section: Introductionmentioning
confidence: 99%